Integration-based extraction and visualization of jet stream cores - Bösiger, Lukas; Sprenger, Michael; Boettcher, Maxi; Joos, Hanna; Günther, Tobias (Geoscientific Model Development, 2022)
Jet streams are fast three-dimensional coherent air flows that interact with other atmospheric structures such as warm conveyor belts (WCBs) and the tropopause. Individually, these structures have a significant impact on the midlatitude weather evolution, and the impact of their interaction is still a subject of research in the atmospheric sciences. A first step towards a deeper understanding of the meteorological processes is to extract the geometry of jet streams, for which we develop an integration-based feature extraction algorithm. Thus, rather than characterizing jet core line purely as extremal line structure of wind magnitude, our core-line definition includes a regularization to favor jet core lines that align with the wind vector field. Based on the line geometry, proximity-based filtering can automatically detect potential interactions between WCBs and jets, and results of an automatic detection of split and merge events of jets can be visualized in relation to the tropopause. Taking ERA5 reanalysis data as input, we first extract jet stream core lines using an integration-based predictor-corrector approach that admits momentarily weak air streams. Using WCB trajectories and the tropopause geometry as context, we visualize individual cases, showing how WCBs influence the acceleration and displacement of jet streams, and how the tropopause behaves near split and merge locations of jets. Multiple geographical projections, slicing, as well as direct and indirect volume rendering further support the interactive analysis. Using our tool, we obtained a new perspective on the three-dimensional jet movement, which can stimulate follow-up research. Copyright:
CRIS-Team Scopus Importer:2022-02-25